Expression of miR-373 and its predicted target genes E-cadherin and CD44 in patients with laryngeal squamous cell carcinoma - Timirci-Kahraman, í–zlem; Verim, Ayşegül; Farooqi, Ammad Ahmad; Turan, Saime; í–zkan-Küçük, Nazli Ezgi; Yaylim, ć°lhan (Cellular and Molecular Biology, 2017)
Laryngeal squamous cell carcinoma (LSCC) is a genomically complex disease that is difficult to target, and efforts have been made to identify new treatment strategies and molecular markers that might stratify patients and individualize options for treatment. miR-373 has diametrically opposed roles in different stages and types of cancers. miR-373 has been suggested to quantitatively control E-cadherin and CD44 expression. We studied the expression of miR-373, E-cadherin and CD44 in laryngeal squamous cell carcinoma and evaluated the association between the disease and clinical characteristics of patients. Tumor tissues were collected from 24 laryngeal cancer patients. Adjacent normal tissue samples were also obtained as controls. After RNA isolation, we assessed the miR-373, E-cadherin and CD44 levels. As endogenous controls, we used the small RNA U6 and GAPDH TaqMan® to normalize the levels of expression of miR-373, E-cadherin and CD44. The fold change in the expression of the genes in larynx tumor and control tissues was calculated using the 2-Î”Î”CT method. miR-373 was significantly upregulated in seventeen tumor samples compared to controls. However, the expression levels of both E-cadherin and CD44 mRNA were found to be significantly downregulated in tumor versus control regions (p=0.026 and p=0.005, respectively). We did not find any significant difference in the expression levels of miR-373, E-cadherin or CD44 and cancer risk factors. miR-373, E-cadherin and CD44 may be involved in the etiopathogenesis of laryngeal cancer. It can be suggested that E-cadherin and CD44 are functional targets of miR-373, but we need further studies to investigate this hypothesis.